(untitled) (Intent Research Scientific Journal, 2023)
The article is devoted to the study of discourse markers in political speech through analyzing the speech of the American president, Barack Obama, depending on Hyland and Tse’s (2004) classification of discourse markers; interpersonal and textual markers. The results show that these discourse markers function as means of social interaction aimed at influencing the nation. Moreover, the article aims to gain a deeper understanding in the translation of introductory discourse markers into the Uzbek language